2021
DOI: 10.1016/j.eclinm.2021.101142
|View full text |Cite
|
Sign up to set email alerts
|

Bullying victimisation in adolescence: prevalence and inequalities by gender, socioeconomic status and academic performance across 71 countries

Abstract: Background: Bullying victimisation is of global importance due to its long-term negative consequences. We examined the prevalence of victimisation and its inequalities in 15-year-olds across 71 countries. Methods: Data were from the Programme for International Student Assessment (March-August 2018). Students reported frequencies of relational, physical, and verbal victimisation during the last 12 months, which were analysed separately and combined into a total score. Prevalence of frequent victimisation (> a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 25 publications
5
26
2
3
Order By: Relevance
“…It is worth noting that the lowest level ratings are associated with bully/victim behaviors, followed by the bully role, which can be explained or justified by the characteristics of the group to which they tend to belong. In other words, finding yourself in these roles within bullying means higher levels of Machiavellianism and being perceived as popular among peers, although Mariko Hosozawa [ 49 ] finds that students with lower academic performance were more likely to be victimized.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the lowest level ratings are associated with bully/victim behaviors, followed by the bully role, which can be explained or justified by the characteristics of the group to which they tend to belong. In other words, finding yourself in these roles within bullying means higher levels of Machiavellianism and being perceived as popular among peers, although Mariko Hosozawa [ 49 ] finds that students with lower academic performance were more likely to be victimized.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible to develop hypotheses about whether separate components, in general, would work better for some. We expected that (1) children below 12 years benefited more from school-based antibullying intervention components than those above 12 years, based on research that showed that anti-bullying interventions become less effective from grade eight onwards and may then even induce iatrogenic effects, possibly because current anti-bullying interventions do not meet adolescencespecific needs for status and respect (Yeager et al, 2015(Yeager et al, , 2018; (2) boys benefited more from school-based antibullying intervention components than girls, as research has shown that interventions may gravitate towards visible, more explicit-typically male-bullying (Barbero et al, 2012;Volk et al, 2012); (3) school-based anti-bullying interventions are more effective for ethnic majority than minority youth, because interventions generally do not attend to ethnicityrelated issues, such as race and ethnicity-based stereotype harassment (Peguero & Williams, 2013;Vervoort et al, 2010;Yeager et al, 2015); (4) youth with higher socioeconomic status (SES) benefited more from school-based antibullying interventions than youth with lower SES, as lower SES youth may need a relatively intense intervention since they might be more likely to engage in bullying or to become victimized, although this might be different across countries (Hosozawa et al, 2021;Tippett & Wolke, 2014); and (5) youth who bully or who are victimized prior to intervention benefited more from school-based anti-bullying interventions, based on research that showed intervention effects to be larger for those victimized or bullied before the intervention (e.g., Ferguson et al, 2007;Juvonen et al, 2016-for an exception, see Kaufman et al, 2018). This suggests that interventions are more relevant and engaging for youth with more severe problems, who may also have more room for behavior change.…”
Section: What Work For Whom?mentioning
confidence: 99%
“…Estos resultados refuerzan el debate sobre la diferencia entre los sexos en lo que respecta a la participación en situaciones de violencia entre pares (3,(10)(11) .…”
Section: Los Resultados Del Health Behaviour In School-agedunclassified
“…En todos los países del mundo existen altas prevalencias de bullying en el ambiente escolar (10)(11) .…”
Section: Introductionunclassified